Pengembangan Media Pembelajaran SIPEKA Berbasis Articulate Storyline 3 Untuk Siswa Kelas 3 Sekolah Dasar - Nuraini, Fatika; Arisyanto, Prasena; Widyaningrum, Ari (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The aim of the research is to develop learning media for grade 3 mathematical fraction educational games (SIPEKA) based on articulate storyline 3. The method in this research is Research and Development (R&D), the ADDIE development model, namely: Analysis, Design, Development, Implementation, Evaluations. Qualitative and quantitative descriptive data analysis techniques. This media has been tested by several experts, namely media experts, material experts, students and grade 3 teachers as media users. Data collection was carried out by interviews, questionnaires and observations. The results of media validation by media experts received a percentage of 96.25% with very decent qualifications, material experts in this media obtained very decent qualifications with a percentage of 91.25%. Apart from validation by experts, SIPEKA Media has been implemented for teachers and students in grade 3 of SD N Bugangan 01. From the results, teacher responses received a percentage of 98.95% and student responses were 99.60%. The results of this research indicate that the development of educational learning media for mathematics fractions is suitable for use by teachers and students in grade 3 elementary schools.